As fronteiras do ensino superior: narrativas de surdos sobre acessibilidade na pós-graduação - Veiga, Filipe Augusto da (2024)
This study addresses the accessibility of deaf students in stricto sensu graduate studies, focusing specifically on public institutions of higher education in the state of Paraná, Southern Brazil. The main hypothesis is that the lack of public exams for Libras interpreters compromises the continuity of accessibility for deaf people, limiting their academic development. Academic papers on the presence of deaf people in graduate studies are still scarce, with most research focused on elementary and undergraduate education. The goals of this study include identifying the accessibility needs of deaf persons in graduate school, proposing solutions and analyzing whether there is continuity in inclusive policies. The methodology is qualitative narrative analysis, carried out from a semi-structured interview in Libras, about the experiences of three female, master’s, and doctoral students. The interviews were recorded and then translated from Libras into written Portuguese. The narratives point to the absence of consistent public policies to ensure accessibility for the deaf, evidencing a gap in academic practices. The hypothesis was confirmed that, without Libras interpreters available, the process of inclusion is compromised, with negative impacts on the academic development of deaf students. In addition, the study points out structural challenges and the lack of awareness of the academic community about the needs of deaf students, reflecting a distance between public policies and educational practice. As a result, the importance of legislative and structural actions to ensure full inclusion is highlighted, such as the creation of adequate spaces for communication in Libras, appreciation of this language and the implementation of public policies that meet the needs of the deaf in higher education.